2011
DOI: 10.1128/aem.01215-10
|View full text |Cite
|
Sign up to set email alerts
|

Concentration and Diversity of Uncultured Legionella spp. in Two Unchlorinated Drinking Water Supplies with Different Concentrations of Natural Organic Matter

Abstract: The estimation of the average value of total species richness (Chao1) in supply A (153) was clearly higher than that for supply B (58). In each supply, about 77% of the sequences showed <97% similarity to described species. Sequences related to L. pneumophila were only incidentally observed. The Legionella populations of the two supplies are divided into two distinct clusters based on distances in the phylogenetic tree as fractions of the branch length. Thus, a large variety of mostly yet-undescribed Legionell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 37 publications
(47 reference statements)
4
58
1
2
Order By: Relevance
“…These results suggest that the AOC levels in drinking water relate to the presence of L. pneumophila. Our results are consistent with results from a previous study where L. pneumophila was detected in a distribution system that was fed with drinking water with a high concentration of natural organic matter (NOM) but not in a distribution system that was fed with drinking water having a low NOM concentration (50). P. aeruginosa and S. maltophilia were also sporadically observed in drinking water, but these organisms were present in drinking water with high or low concentrations of AOC and TOC.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These results suggest that the AOC levels in drinking water relate to the presence of L. pneumophila. Our results are consistent with results from a previous study where L. pneumophila was detected in a distribution system that was fed with drinking water with a high concentration of natural organic matter (NOM) but not in a distribution system that was fed with drinking water having a low NOM concentration (50). P. aeruginosa and S. maltophilia were also sporadically observed in drinking water, but these organisms were present in drinking water with high or low concentrations of AOC and TOC.…”
Section: Discussionsupporting
confidence: 82%
“…However, L. pneumophila could not be cultivated from drinking water samples that were positive for the mip gene of L. pneumophila. Similar results were reported for unchlorinated drinking water sampled from the distribution systems of two groundwater treatment plants in the Netherlands (50). However, in contrast to our findings, the mip gene copy numbers observed in that study were below the detection level of the culture method, which could explain the observed differences between qPCR and cultivation results.…”
Section: Discussioncontrasting
confidence: 57%
“…Consequently, cultivation-based methods provide a limited view of NTM diversity in drinking water. The observation that most NTM in unchlorinated drinking water have not yet been cultivated, and may not be cultivable, is consistent with observations made for other microorganisms in unchlorinated drinking water such as Legionella (29), protozoa (46), and fungi (37).…”
Section: Discussionsupporting
confidence: 72%
“…Subsequently, the filter was added to phosphate and MT buffer of a FastDNA Spin kit for soil (Qbiogene) and a DNA fragment of an internal control was included before the buffer with filter was stored at Ϫ20°C. The internal control was used to determine the recovery efficiency of DNA isolation and PCR analysis (28,29). DNA was isolated using a FastDNA Spin kit for soil according to the supplier's protocol and eluted in 200 l elution buffer.…”
Section: Methodsmentioning
confidence: 99%
“…An extensive collection of case studies and research articles dating back Ͼ30 years demonstrates the adaptability and potential of legionellae to colonize man-made aquatic environments ( Fig. 1), from the initial point of water treatment (69)(70)(71)(72)(73) to private homes (74)(75)(76)(77)(78), hospitals (79)(80)(81)(82)(83), restaurants (84,85), bath houses (86)(87)(88)(89), hotels (90)(91)(92), and, eventually, wastewater facilities (93,94). These studies underscore the resiliency and persistence of legionellae.…”
Section: Physiology and Ecologymentioning
confidence: 99%